The memory-less method of generating multiplicative inverse values for S-box in AES algorithm - Siti Zarina, Md Naziri; Norina, Idris (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org